2010
DOI: 10.3109/17453674.2010.483987
|View full text |Cite
|
Sign up to set email alerts
|

Slipped capital femoral epiphysis: an ultrastructural study before and after osteosynthesis

Abstract: Background and purposeSeveral different theories have been proposed to explain the pathogenesis of slipped capital femoral epiphysis (SCFE). Using transmission electron microscopy (TEM), we carried out an ultrastructural study of core biopsy specimens of the physis at various stages of the disease.MethodsCore biopsies were performed in 6 patients with different forms of SCFE during the first operation, and in 3 of them when removing the osteosynthesis material before physeal closure. The specimens were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
0
19
0
3
Order By: Relevance
“…The amount of proteoglycans in the ECM was moderately decreased in the matrix of the physis in SCFE compared to normal [3,7,9]. Also, abnormal proteoglycans were found [5].…”
Section: Histological Changes In Scfementioning
confidence: 92%
See 2 more Smart Citations
“…The amount of proteoglycans in the ECM was moderately decreased in the matrix of the physis in SCFE compared to normal [3,7,9]. Also, abnormal proteoglycans were found [5].…”
Section: Histological Changes In Scfementioning
confidence: 92%
“…Interestingly, Adamczyk et al showed that apoptosis was increased throughout the physis in SCFE, in contrast with controls, where apoptosis was found only in the hypertrophic zone [8]. The chondrocytes showed intracellular abnormalities [5,7,9]. An increase in the nuclear and cytoplasmic density was seen in the proliferative and hypertrophic chondrocytes with SCFE and an increase in cytoplasmic glycogen [7,9].…”
Section: Histological Changes In Scfementioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural analysis shows slippage of the physis occurs secondary to weakness of the supporting fibrous network caused by collagen disturbance [2,19,57]. Mechanical [4,20,45,68], endocrine [52,85,86], and metabolic disorders of puberty [60] have been postulated to cause the pathological disturbance in the growth plate that ultimately fail mechanically and slip.…”
Section: Search Strategies and Criteriamentioning
confidence: 99%
“…It could be hypothesized that these aspects of the fibrocartilage are the result of tissue weakness due to a physiopathologic modification during pubertal growth as reported in slipped capital femoral epiphyses (SCFE) (18,19).…”
Section: Discussionmentioning
confidence: 99%